Credit risk management practice in nonbanking financial institutions: a study on Lanka Bangla Finance limited - Abid, Amzad Sadik (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.